2012
DOI: 10.3389/fpsyg.2012.00482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Empathic Paraphrasing – Extrinsic Emotion Regulation in Social Conflict

Abstract: In the present study, we investigated the effects of empathic paraphrasing as an extrinsic emotion regulation technique in social conflict. We hypothesized that negative emotions elicited by social conflict can be regulated extrinsically in a conversation by a listener following the narrator’s perspective and verbally expressing cognitive empathy. Twenty participants were interviewed on an ongoing or recently self-experienced social conflict. The interviewer utilized 10 standardized open questions inviting par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 65 publications
4
27
0
7
Order By: Relevance
“…The primary mechanisms provided in the literature to explain the underlying benefits of communicating perspective is that it fosters a greater sense of ‘feeling heard’, and mutual understanding (Ames, 2008; Ames & Wazlawek, 2014; Bruneau & Saxe, 2012; Howieson & Priddis, 2011; Lee et al, 2015). It also fosters a sense of openness, transparency, and honesty that maximises perceived politeness and minimises perceived hostility (Howieson & Priddis, 2015; Ingerson, DeTienne & Liljenquist, 2015; Kellas, Willer & Trees, 2013; Kidder, 2017; Seehausen et al, 2012). The primary mechanisms to explain a benefit of I-language over you-language are that I-language indicates a recognition of providing a specific point of view that is open for discussion (Burr, 1990), and that you-language can at times be perceived as accusatory (Kubany et al, 1992a, 1992b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary mechanisms provided in the literature to explain the underlying benefits of communicating perspective is that it fosters a greater sense of ‘feeling heard’, and mutual understanding (Ames, 2008; Ames & Wazlawek, 2014; Bruneau & Saxe, 2012; Howieson & Priddis, 2011; Lee et al, 2015). It also fosters a sense of openness, transparency, and honesty that maximises perceived politeness and minimises perceived hostility (Howieson & Priddis, 2015; Ingerson, DeTienne & Liljenquist, 2015; Kellas, Willer & Trees, 2013; Kidder, 2017; Seehausen et al, 2012). The primary mechanisms to explain a benefit of I-language over you-language are that I-language indicates a recognition of providing a specific point of view that is open for discussion (Burr, 1990), and that you-language can at times be perceived as accusatory (Kubany et al, 1992a, 1992b).…”
Section: Resultsmentioning
confidence: 99%
“…For example, by explicitly stating what you perceive is the other’s point of view by saying something like ‘What I’m hearing is that perhaps you aren’t seeing enough evidence of appreciation and so feel like you’re being taken for granted’. Seehausen et al (2012) demonstrated the utility of paraphrasing by interviewing participants (interviewees) about a recent social conflict while varying interviewer responses across participants as simple note taking or paraphrasing. Interviewees receiving paraphrase responses reported feeling less negative emotion associated with the conflict compared to interviewees receiving note taking responses.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that distinct IER strategies may have maladaptive or adaptive consequences, depending on the domain assessed. For instance, one experiment compared an extrinsic IER strategy (empathic paraphrasing) to a control condition (note-taking) and examined the subjective and physiological consequences on targets following a discussion of social conflict [34]. Results demonstrated that, in response to paraphrase, participants exhibited higher physiological arousal, but lower vocal intensity and self-reported distress.…”
Section: Identifying Adaptive and Maladaptive Interpersonal Emotion Rmentioning
confidence: 97%
“…Petroni et al (2011) found that the recognition of face valence is associated to the ability to read others' intentions. EP has also been linked to responses during social conflicts (Seehausen et al, 2012, 2014). Taken together this evidence suggests that EP is crucial for rapidly and accurately scanning the environment in the search of cues that can trigger adaptive social responses.…”
Section: Introductionmentioning
confidence: 99%